We Have Come to Stay and We Shall Find All Means to Live and Work in this Country: Nigerian Migrants and Life Challenges in South Africa - Adediran Daniel Ikuomola; Johan Zaaiman (Etnoantropološki Problemi, 2014)
In recent times many Nigerians have been singled out when it comes to criminal activities and xenophobic attacks in South Africa, which leads to disruption of the hitherto cordial relationship between South African host communities and Nigerian migrants. Nevertheless, the rate of Nigerians migrating to South Africa keeps soaring. Studies of migration between Nigeria and South Africa, have been scanty, often limited to the study of traditional economic disparity between the two countries with less emphasis on the social-cultural challenges facing Nigerian migrants in the host communities. This paper thus examined the socio-economic and cultural challenges facing Nigerian migrants in selected communities in Johannesburg, South Africa. Data for the study were collected through in-depth interviews and focus group discussions with Nigerian migrants in Hillbrow, Braamfontein and Alexandra suburbs in Johannesburg, South Africa.